Effect of wing flexibility on flight dynamics stability of flapping wing MAVs in forward flight. Issue 3 (September 2016) - Xue, Dong; Song, Bifeng; Song, Wenping; Yang, Wenqing
The paper presents a qualitative study of the effect of the wing flexibility on the flight stability of flapping wing micro air vehicles in forward flight. The longitudinal dynamic flight stability is compared between rigid wing flapping wing micro air vehicles and flexible-wing flapping wing micro air vehicles. The aerodynamics derivatives are computed respectively using the method of computational fluid dynamics and fluid–structure interaction method, and the techniques of eigenvalue and eigenvector analysis are applied to solve the equations of motion. It is shown that the flexibility can change the stability properties of the flapping micro air vehicles from unstable to stable. Besides, the position of mass center of flapping micro air vehicles is also a key factor to the flight stability, which provides a new insight to design a stable flapping wing micro air vehicle.